MUTU DAN DAYA SIMPAN BUAH TOMAT (Solanum lycopersicum L.) ENAM GALUR HARAPAN GENERASI M9 YANG DIHASILKAN DI DATARAN TINGGI - , GITA TRIANTIKA, Erlina Ambarwati, S.P., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is a part of long efforts to develop superior pure line tomato varieties. It has been started in 2001 by mutation induction of âIntanâ variety using Gamma Co-60 radiation. The current research was aimed to evaluate shelf life and fruit quality of selected promising lines of Co-60 irradiated tomatoes in M9 generation produce in the highland. There are 6 selected promising lines of tomatoes (G20 1/13/25/28/16/13/5, G20 1/13/25/26/24/11/16, G40 2/19/9/19/12/13/7, G40 2/15/23/22/13/13/6, G60 3/9/12/34/12/14/16, and G40 3/15/15/1/13/6/9) include control variety, i.e. âIntanâ and check variety, i.e. âFortunaâ (F1 hybrid) which were planted in Completely Randomized Block Design with four blocks as replications at the highland located in Ngipiksari, Sleman (714 m above the sea level) and in the Laboratory of Horticulture, Faculty of Agriculture, Gadjah Mada University, Yogyakarta in May until September 2012. Data of physical and chemical characteristics, and shelf life of tomato fruit were collected and analyzed using ANOVA and DMRT at ï¡ = 5%. The result showed that G20 1/13/25/26/24/11/16 had fruit weight and fruit volume higher than âIntanâ and âFortunaâ